Development of Powtoon Video Media in Geography Subjects - Wijayanti, Detti; Suasti, Yurni; Ernawati, Ernawati (International Journal of Educational Dynamics, 2022)
The teaching and learning process is a process of reciprocal interaction between students and teachers and between students to achieve learning objectives. This research was conducted at SMA Negeri 1 Sungai Rumbai using research and development methods or often called Research and Development (R&D). The results of the research obtained are that the Powtoon learning video learning media is declared very feasible after analyzing data processing using Microsoft Excel so that the total score is 383 with a mean level of 4.89 and a percentage level of 98% with the predicate "Very feasible". declared practical after processing the research data obtained from the questionnaire, and a practicality test was carried out so that a total score of 2891 was obtained with a mean level of 4.93 and a percentage of 93% in the "Very Practical" category.